A cartografia urbana na análise morfogenética de espaços urbanos : o caso do eixo da Boavista na cidade do Porto - Fernandes, Mário Gonçalves (2021)
Starting from a morphogenetic study of the Boavista axis, in the city of Oporto, a comparative analysis of the characteristics of the urban cartographic documents used (about two dozen surveys/projects, dating from the late 18th century to the beginning of the 20th century) and emphasizes the use of ancient urban cartography as an important tool for knowledge and recognition of urban morphogenesis, such as a framework of current urban action. The Boavista axis corresponds to a notable straight segment (consisting of a street, an avenue, a rectangular square and two roundabouts) that extends for about 6.5 kilometers, evidencing an intermediate roundabout and presenting two typologically different cross profiles. Being one of the elements that are most evident in the urban network of Porto and which looks like the result of a single planning feature, the Boavista axis is also notable because it was built between the 18th and 20th centuries, corresponding to the political persistence of several generations of municipal power. Contrary to its form, its history is not linear and although considering the course of Rua da Boavista as the genesis conditioning the layout of the Avenida da Boavista, each (street and avenue) evokes distinct urban designs, based on different territorial and urban strategies. The formation of the Boavista axis between 1784 and 1915/17 was more complex, but urban cartography allows identifying each of its structuring periods, either by identifying the physical elements that identify the phasing process, or by the intrinsic characteristics of the various documents cartographic.